THE REALITYOF APPLYING GOVERNANCE PRINCPLES IN GENERAL EDUCATION IN SUDAN - Bashir, Mohammed Hassan (Journal of Educational and Psychological Sciences, 2019)
The aim of this paper is to identify the theoretical bases of governance and its importance، to identify the reality of implementing the principles of governance in education in Sudan، and to learn about the most important requirements of applying the principles of governance in education. The researcher used the descriptive analytical descriptive approach in the study by listing and tracking information about governance and its applicability in Sudanese educational institutions. The paper reached a number of results، the most important of which are: The reality of the implementation of the principles of government in education is weak; especially the principle of transparency، participation and accountability is less applicable. "In the light of these results، the researcher recommended a number of recommendations، the direction of officials in the Ministry of Education and the development of the organizational structures of the Department of Education to accommodate the new management trends including governance، and to promote transparency، accountability and participation.